2010
DOI: 10.1021/ja100403a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Peptide Space for Enzyme Modulators

Abstract: Enzymes which regulate the metabolic reactions for sustaining all living things, are the engines of life. The discovery of molecules that are able to control enzyme activity is of great interest for therapeutics and the biocatalysis industry.Peptides are promising enzyme modulators due to their large chemical diversity and the existence of well-established methods for library synthesis.Microarrays represent a powerful tool for screening thousands of molecules, on a small chip, for candidates that interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Even the transfer of substrates between enzymes can utilize unstructured interactions to keep the local concentration of product/substrate high and facilitate transfer [11]. Indeed, protein interactions in biology almost certainly represent a continuum between structurally defined interactions with long residence times and transient unstructured interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Even the transfer of substrates between enzymes can utilize unstructured interactions to keep the local concentration of product/substrate high and facilitate transfer [11]. Indeed, protein interactions in biology almost certainly represent a continuum between structurally defined interactions with long residence times and transient unstructured interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial peptide selection can generate not only material-binding peptides, but also peptides having affinity for certain proteins, such as Fc region of IgG [211213] and enzymes (namely horseradish peroxidase, alkaline phosphatase and β-Gal β-galactosidase) [214216]. Jung et al demonstrated that highly oriented layer of antibodies was obtained when immobilized on gold SPR chips coated with Fc-specific peptides.…”
Section: Antibody Immobilization Chemistriesmentioning
confidence: 99%
“…Microarrays of 10,000 20-mer peptides were produced by Arizona State University as previously reported [14,17]. Briefly, 10,000 distinct polypeptide sequences were spotted in duplicate onto a glass slide possessing an amino-silane surface coating.…”
Section: Materials and Approachmentioning
confidence: 99%
“…These arrays can be made by printing pre-synthesized peptides [14], SPOT synthesis (spotting and synthesis) [15], and light-directed, spatially-addressable synthesis [16]. Hydrogel-coated peptide microarrays were also reported as a means of screening for enzyme activity that is modulated by specific protein–peptide interactions, and has made it possible to perform activity assays using high-density microarrays [17]. …”
Section: Introductionmentioning
confidence: 99%